Natural Fabrications Science, Emergence and Consciousness - Seager, William; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The spectacular success of the scientific enterprise over the last four hundred years has led to the promise of an all encompassing vision of the natural world. In this elegant picture, everything we observe is based upon just a few fundamental processes and entities. The almost infinite variety and complexity of the world is thus the product of emergence. But the concept of emergence is fraught with controversy and confusion. This book ponders the question of how emergence should be understood within the scientific picture, and whether a complete vision of the world can be attained that includes consciousness.
The Scientific Picture of the World -- Looking Out -- Looking In -- Consciousness in the Brain -- Emergence and Consciousness -- Emergence and Cellular Automata -- Against Radical Emergence -- Emergence and Supervenience -- Generalized Epiphenomenalism -- The Paradox of Consciousness -- Embracing the Mystery.
Keywords: Physics; Philosophy of mind; Neurobiology; Psychology, clinical; Physics; Statistical Physics, Dynamical Systems and Complexity; Philosophy of Mind; Neurobiology; Neuropsychology